Al-Qur’an dan Hadist - Purwaningsih, Yuli; Mahmudi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The Qur'an and Hadith have a complementary relationship. The Qur'an provides basic instructions and general principles, while the Hadith offer detailed explanations and concrete examples from the life of the Prophet Muhammad SAW. These two sources are used together to understand and practice Islamic teachings as a whole. The Koran is the holy book of Muslims which is considered a direct revelation from Allah SWT, conveyed to the Prophet Muhammad SAW through the Angel Gabriel. Consisting of 114 surahs and thousands of verses, the Qur'an covers aspects of faith, worship, law, ethics and history. Written in Arabic, the Qur'an is considered the greatest miracle of the Prophet Muhammad SAW, renowned for the beauty of its language and the depth of its content. The Qur'an functions as a perfect and eternal guide for the lives of Muslims and the Hadith is a collection of the words, actions and agreements of the Prophet Muhammad SAW conveyed by his companions. Hadith complement the Qur'an by providing detailed explanations of the teachings contained therein. Hadith are categorized based on their authenticity into sahih (authentic), hasan (good), dhaif (weak), and maudhu' (false). The collection and verification of hadiths was carried out by scholars such as Imam Bukhari and Imam Muslim, who ensured the reliability and authenticity of the hadiths.